The Role of Digital Management in Activating Administrative Communication among Female Administrators in Secondary Schools in Hail City - Albaqawi, Modi Meshrif Sber (Journal of Educational and Psychological Sciences, 2019)
The study aimed at identifying the role of digital management in activating administrative communication among female administrators in secondary schools in Hail City from the female administrators' perspective, and identifying the obstacles of applying digital management in the administrative communication process in the secondary schools of Hail City from the female administrators' perspective.It also aimed at revealing significant statistical differences which are due to the variables of (Qualifications, years of service, technology related training courses received).The study used the survey descriptive method, and the questionnaire as data collecting tool. It was applied to a study sample of (244) female administrators in the general secondary schools in Hail City. The study used theThe study has reached the following results:- The role of digital management in activating administrative communication among female administrators has come with a general average of (2.76/4) (medium).- The obstacles of applying digital management in the administrative communication process in the secondary schools from the female administrators' perspective has come with a general average of (3.59/4) (high).- There were statistically significant differences at function level (α≤0.05) according to the variable of qualifications in favor of those who have received Bachelor degree or Diploma, and according to the variable of number of technology related training courses received in favor of those who have received two courses or more contra those who did not receive any training. There were no statistically significant differences according to the variable of years of experience.In light of the results, the study has reached number of recommendations as following:- Provision of evidences and instructions required to explain the mechanism of handling new programs;- Spreading the concept of digital management;- Attracting distinctive human competencies in the digital management field;- Holding training courses in order to raise female administrators’ efficiency.
Keywords: digital management; administrative communication; administrators; secondary school; the city of Hail